The Effect of Tool Rotational Speed and Welding Configuration on the Mechanical Properties of High Density Polyethylene (HDPE) Plate Friction Stir Welded Joint - Nugroho, Aris Widyo; Arifin, Arifin; Imbaraga, M. Rafiudin; Rahman, Muhammad Budi Nur (Universitas Muhammadiyah Yogyakarta, 2024)
The study investigates the impact of tool rotational speed and welding configuration on the mechanical properties of friction stir welded joints of HDPE plates. The plates were cut into rectangular shapes and clamped on a metal plate for FSW welding. Two welding configurations were used: single-side welding (SS) and double-side welding (DS), with rotational speeds of 900, 1500, and 2000 rpm. The plates were subjected to tensile and bending tests, and angular distortion was also measured. The findings suggest that decreasing the tool's rotational speed to 900 rpm and using double-side welding reduces angular distortion and improves tensile and flexural strength. The study emphasizes the importance of defect reduction techniques in improving the mechanical properties of HDPE FSW joints.